2001
DOI: 10.1097/00000658-200107000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Gastric Bypass in Morbidly Obese Patients With Severe Venous Stasis Disease

Abstract: ObjectiveTo determine the risks and benefits of gastric bypass-induced weight loss on severe venous stasis disease in morbid obesity. Summary Background DataSevere obesity is associated with a risk of lower extremity venous stasis disease, pretibial ulceration, cellulitis, and bronze edema. MethodsThe GBP database was queried for venous stasis disease including pretibial venous stasis ulcers, bronze edema, and cellulitis. ResultsOf 1,976 patients undergoing GBP, 64 (45% female) met the criteria. Mean age was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(47 citation statements)
references
References 19 publications
1
45
0
1
Order By: Relevance
“…In our patient population, increasing weight was not only associated with an elevated VCSS but also with other obesity-related problems such as hypertension and diabetes. Sugerman et al 18 found that severe venous stasis disease was associated with significantly greater weight, BMI, male gender, age, comorbidity, and surgical risk. After gastric bypass surgery, the weight loss corrected the venous stasis disease as well as the other obesity-related problems in almost all patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient population, increasing weight was not only associated with an elevated VCSS but also with other obesity-related problems such as hypertension and diabetes. Sugerman et al 18 found that severe venous stasis disease was associated with significantly greater weight, BMI, male gender, age, comorbidity, and surgical risk. After gastric bypass surgery, the weight loss corrected the venous stasis disease as well as the other obesity-related problems in almost all patients.…”
Section: Discussionmentioning
confidence: 99%
“…With a protocol consisting of early ambulation, compression stockings, intermittent compression stockings, and enoxaparin, a low rate of postoperative venous thromboembolism was described (74). In patients at especially high risk for venous thromboembolism (e.g., patients: older than 65 years, BMIO50, a previous venous thromboembolism, venous insufficiency, sleep apnea), placement of a vena cava filter as well as a prolonged course of oral anticoagulants should be seriously considered (75)(76)(77)(78).…”
Section: Postoperative Complications and Difficultiesmentioning
confidence: 99%
“…Risk factors for DVT/PE include history of a prior thromboembolic event, central fat distribution, and smoking (34); female gender and age (31); venous stasis, venous insufficiency, and OSA (35); hypercoagulable state; and use of oral contraceptives. Data suggest perioperative benefit from placement of inferior vena cava filters in high-risk patients (7,36).…”
Section: Dvt/pementioning
confidence: 99%
“…Approximately two-thirds of early postoperative mortality from WLS is associated with anastomotic leaks and PEs (5)(6)(7)(8)(9)(10). Potential long-term problems include not only those seen after any abdominal procedure, such as ventral hernia, but also those specific to WLS procedures, e.g., gastric outlet obstruction, marginal ulceration, bowel obstruction, protein malnutrition, and vitamin deficiencies (3).…”
Section: Introductionmentioning
confidence: 99%